Wearable Nail Deformation Sensing for Behavioral and Biomechanical Monitoring and Human-Computer Interaction. Issue 1 (December 2018) - Sakuma, Katsuyuki; Abrami, Avner; Blumrosen, Gaddi; Lukashov, Stanislav; Narayanan, Rajeev; Ligman, Joseph; Caggiano, Vittorio; Heisig, Stephen
Abstract The dynamics of the human fingertip enable haptic sensing and the ability to manipulate objects in the environment. Here we describe a wearable strain sensor, associated electronics, and software to detect and interpret the kinematics of deformation in human fingernails. Differential forces exerted by fingertip pulp, rugged connections to the musculoskeletal system and physical contact with the free edge of the nail plate itself cause fingernail deformation. We quantify nail warpage on the order of microns in the longitudinal and lateral axes with a set of strain gauges attached to the nail. The wearable device transmits raw deformation data to an off-finger device for interpretation. Simple motions, gestures, finger-writing, grip strength, and activation time, as well as more complex idioms consisting of multiple grips, are identified and quantified. We demonstrate the use of this technology as a human-computer interface, clinical feature generator, and means to characterize workplace tasks.